2012
DOI: 10.1590/s0101-20612012005000007
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characteristics and functional properties of vitabosa (mucuna deeringiana) and soybean (glycine max)

Abstract: Physicochemical characteristics and functional properties of vitabosa flour (Mucuna deeringiana) and soybean flour (Glycine max) were determined. Oil absorption capacity was higher in vitabosa. Water absorption capacity was higher in soy and it was affected by the change in the ionic strength of the medium. Emulsifying Activity (EA) decreased with increasing concentration of flour, while Emulsifying Stability (ES) showed an increased. EA and ES of flours have more ionic strength in the range between 0.0 and 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 34 publications
1
7
0
1
Order By: Relevance
“…Also, Ogodo et al who reported increase in OHC of maize flour fermented with LAB consortium which is in agreement with the present investigation [22]. However, the result of this study is higher than 1.43 ml/g reported by [1] for soybean. The increase in the OHC of the present study suggests that the flour could be useful in food formulation where an oil holding capacity is considered [6].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also, Ogodo et al who reported increase in OHC of maize flour fermented with LAB consortium which is in agreement with the present investigation [22]. However, the result of this study is higher than 1.43 ml/g reported by [1] for soybean. The increase in the OHC of the present study suggests that the flour could be useful in food formulation where an oil holding capacity is considered [6].…”
Section: Discussionsupporting
confidence: 93%
“…In developing countries of Africa like Nigeria, malnutrition in terms of protein is prevalent due to inadequate or high cost of meat and milk, hence the need for alternative sources of protein [1]. Legumes such as Bambara groundnut pigeon pea, soybeans are nutritious foods which can serve as an alternative to animal proteins owing to their reported nutritional attributes [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Emulsification capacity (EC) and emulsion stability (ES) were determined according to Chaparro Acuña, Gil González [ 30 ] with some modifications. Flour samples (0.4 g), 20 ml of maize oil (0.9 ml/g) and 20 ml water (1.0 ml/g) (resulting in a 1% (w/v) mixture) were homogenized for 1 min using a Waring blender at low speed.…”
Section: Methodsmentioning
confidence: 99%
“…The region of the minimum solubility of proteins (isoelectric region) was the region of least soluble and minimum emulsifying capacity. The emulsifying properties vary with the two effects (1) absorption of the protein at oil or water interface results in a substantial decrease in interfacial energy (2) structural, electrostatic and mechanical energy barriers are caused by the interfacial layer that opposes destabilization (Chaparro Acuña, Gil González & Aristizábal Torres, 2012;Kumar et al, 2011). This property makes both EA and ES opposite to each other.…”
Section: Represents Thatmentioning
confidence: 99%